Logical frameworks - Huet, Gérard; Plotkin, G. 1946- (Cambridge University Press, 1991)
This 1991 volume contains the proceedings of the first international workshop on Logical Frameworks. The contributions are concerned with the application of logical reasoning and proof theory in computer science and its relevance to automatic theorem proving, and consequently topics such as artificial intelligence. It is the only source for much of this material and will be a necessary purchase for mathematicians and computer scientists undertaking research at the interface of logic and software engineering